(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Forensic anthropology being a speciality for analysing skeletal remains plays a very important part in solving crimes where, the only evidence is bones. Bones, for a forensic scientist is a piece of puzzle when put together meticulously, can reveal a whole story as we will be discussing here with a case report. Some skeletal remains cases1. It is a very interesting process by which a forensic medicine expert/scientist takes each bone as a piece of puzzle which when put together meticulously, reveals a whole story behind them. When skeletal remains are discovered, forensic anthropologists come into play by analysing the bones and the site they are recovered from; to determine the crucial questions of who, how and when regarding the death of the person to whom those bones belong. So the big question being who died and whether any criminality was involved in his death.